Pitch-Derived Carbon-Coated Hierarchical Porous Microspheres Constituted of Zeolitic Imidazolate Framework-8 Derived Hollow N-doped Carbon Nanocages and Si Nanospheres for High-Performance Li–Ion Battery Anodes - Lee, Jae Seob; Oh, Geon Hui; Cho, Chungyeon; Kim, Noeul; Saroha, Rakesh; Jeong, Sang Mun; Shim, Jae Oh; Jung, Dae Soo; Park, Gi Dae; Kang, Yun Chan; Park, Jin Sung; Cho, Jung Sang (Small Structures, 2025)
In this study, an innovative spray-drying-based approach for the design and synthesis of 3D hierarchical porous microspheres comprised of Si nanospheres and zeolitic imidazolate framework-8 (ZIF-8)-derived hollow N-doped carbon nanocages is presented. This sophisticated design of Si-based carbonaceous framework is characterized by the hollow N-doped carbon cages, which can reinforce the electrical conductivity of Si nanosphere, facilitate the electrolyte penetration into the nanostructure, and effectively alleviate the volume changes that occur during cycling. Notably, pitch-derived carbon is coated evenly on the surface of the framework, generating a conformal coating that can effectively encapsulate the Si nanoparticles. The prepared composite microsphere is characterized by the 3D conductive network to which Si nanoparticles are evenly distributed, which play the role of a powerful mixed ion and electron conductor, highly enhancing the electrochemical properties when applied as anodes in lithium–ion batteries. The microspheres exhibit high structural robustness during 500 charge–discharge cycles when cycled at 1.0 A g−1. To validate the practicability, the microspheres are blended with graphite for preparation of anode and coupled with Li(Ni0.8Co0.1Mn0.1)O2 (NCM811) to prepare full cell, which exhibit ≈91% capacity retention after 100 cycles at 0.5 C.
Keywords: carbon coating; lithium–ion batteries; metal-organic framework; silicon; spray drying